Factors Affecting Photo Voltaic Solar Energy Usage Intention in Rural Households in Bangladesh: A Structural Equation Modelling Approach - Alam Syed Shah.; Masukujjaman Mohammad; Lin Chieh-Yu; Omar Nor Asiah.; Na Meng; Othman Abdullah Sanusi (Environmental and Climate Technologies, 2022)
This research examines the factors that affect Photo Voltaic (PV) solar technology’s usage intention in rural households in Bangladesh. The conceptual model for this research was developed according to past studies. There were five hypotheses developed and verified in this study. Cross sectional quantitative method was used in this research. The model was tested using empirical data collected from 209 households. This research mentions that PV solar technology usage intention was predicted by environmental concern, environmental knowledge, adoption cost, awareness, and government initiatives. The model shows a larger proposition (95 %) in the variance of PV solar technology usage in rural households in Bangladesh. According to the results of this study, we have accepted all hypotheses (H1–H5). From a practical perspective, this study’s results provide a guideline for investment decisions for the usage of PV solar technology in Bangladesh.